Optimizing the use of thiopurines in inflammatory bowel disease. (May 2015) - Goel, Rishi M.; Blaker, Paul; Mentzer, Alex; Fong, Steven C.M.; Marinaki, Anthony M.; Sanderson, Jeremy D.
Immunomodulator drugs, of which thiopurines can be considered the backbone, are widely used in the treatment of inflammatory bowel disease. They have been shown to be highly effective and safe; however, a significant proportion of patients are deemed to have a poor response or suffer adverse reactions. Knowing how to monitor and optimize thiopurine therapy in these scenarios is crucial to effective management. We discuss the metabolism of thiopurines, the use of enzyme/metabolite testing to guide treatment, as well as strategies to circumvent toxicity and side effects, such as allopurinol coprescription. The indications, use in pregnancy, safety profile and duration of thiopurine therapy are also discussed.